Atherosclerosis risk factors may be underestimated in patients with pulmonary hypertension associated with congenital heart disease – results of Polish snapshot registry. (14th October 2021) - Mamzer, A; Kopec, G; Kusmierczyk-Droszcz, B; Skowron, W; Mroczek, E; Lewicka, E; Kaminski, K; Karasek, D; Mularek-Kubzdela, T; Mizia-Stec, K; Kurzyna, M; Gasior, Z; et al.
Abstract: Introduction: Classic risk factors of atherosclerosis may contribute to cardiovascular (CV) risk in patients (pts) with pulmonary hypertension associated with congenital heart disease (PAH-CHD), but their prevalence is poorly studied. Purpose: We evaluated a large cohort of Polish PAH-CHD patients (PAHpts) treated with specific therapies with regard to prevalence of classic risk factors for atherosclerosis. Methods: A multicenter observational snapshot registry was conducted under the auspices of Polish Cardiac Society to study PAH pts, identified in centers treating >5 such pts in years 2008–2018. The analysis included 250 PAH-CHD pts, including non-corrected CHD – predominantly Eisenmenger Syndrome (Gr. 1, 224 pts, mean age 42±2 years, 63% females) and pts after heart disease correction (Gr. 2, 26 pts, mean age 42±6.5 years, 62% females). The incidence of classic CV risk factors was compared in both groups. Results: The prevalence of risk factors was considerable considering young age of the cohort and statistically similar in both groups (Figure). Hypertension was present in 14% in Gr. 1 and 15% in Gr. 2. The incidence of diabetes was comparable in both groups (3% vs. 4%). Hyperlipidemia was nearly numerically twice as frequent in Gr. 1 (23% vs. 12%, p=0.18). Current smokers (1%) were only present in Gr. 1, while history of smoking was 4% in both groups. Symptomatic atherosclerosis of peripheral arteries was twice as frequent in Gr. 1 (8% vs. 4%, p=0, 71). There was no difference regarding prior stroke (3, 6% vs 4%, p=0, 63). Chronic kidney disease and atrial fibrillation were one and a half more often in Gr. 1 (respectively, 12% vs. 8%, p=0, 81; 12% vs. 8%, p=0.75). Mean heart rate was 72±2 bpm in Gr. 1 and 77±7 bpm in Gr. 2. Gastrointestinal bleeding was reported only in Gr. 1 (2.7%). SCORE calculated risks were low due to low age, but high risk was identified in 9.3% of Gr. 1 and 20% of Gr. 2 (p=0.096). Conclusions: Based on our data from national survey, classic atherosclerosis CV risk factors are not uncommon in the population of relatively young patients with PAH-CHD, parallel to improved longevity. Selected pts from both groups present with elevated risk of death from atherosclerotic complications. This finding may influence the overall mortality risk in PAH-CHD population and reflects new challenges in management despite progress in specific therapies of pulmonary hypertension. FUNDunding Acknowledgement: Type of funding sources: None.